WAYANG SENI PERSEMBAHAN MENJADI SENI PERTUNJUKAN POPULER - Mardjono Mardjono (Institut Seni Indonesia Surakarta, 2011)
Wayang has been known by Javanese society since olden times before Hindu culture although it was very simple in shape. The main basis why Javanese society performed wayang kulit in olden time was that they believed that the ancestral spirit could be brought back through a magicalreligious ritual hoping that they could help the living. Therefore, the existing wayang kulit performance that has become a spectacle used to be aseries of religious ceremony. Over time wayang kulit performance gradually turns to be an entertainment although the traces of religious ceremonycan be felt. This research does not have an orientation towards the history and development of wayang stories that have developed rapidly because of the puppeteer's creativity. This research is more oriented to wayang performance which was at first a very simple shadow play intended to worship the ancestral spirit. The performance has now developed into a popular performance that remains containing invaluable values.Nowadays it turns to be a commercial performance. To analyze the problems, a historical approach dealing with the growth and development of wayang performance as a means of worship is used. .Key words: wayang, worship, popular.